Negotiating Multimodal Literacy in Madrasah Classrooms: Teachers’ Challenges in Islamic Educational Contexts - Khumaedi, Agus; Fathuddin, Ahmad Ubaedi; Puspitasari, Dewi (Dinamika Bahasa dan Budaya, 2026)
Madrasah education plays a strategic role in shaping students’ religious values, moral character, and literacy practices. However, classroom instruction in many madrasahs remains dominated by text-based and teacher-centered approaches, which can limit students’ opportunities to actively construct meaning. This article explores the implementation of multimodal project-based learning in madrasah classrooms through the lens of Islamic education. Guided by Sociocultural Theory and a narrative inquiry approach, the study examines how multimodal activities, such as drawing, storytelling, and limited digitally supported tasks, support literacy development while allowing teachers to integrate Islamic values into everyday learning practices. Drawing on teachers’ narratives and classroom experiences, the article highlights both the pedagogical possibilities of multimodal learning and the challenges faced by madrasah teachers, including limited resources, curricular rigidity, and emotional demands associated with instructional innovation. The findings suggest that multimodal projects create spaces for more meaningful, and value-oriented literacy practices in madrasah classrooms, positioning teachers as reflective agents who negotiate between curriculum expectations and students’ lived experiences.